Comment la bonne Ligue sauva la monarchie. 1593 selon Nicolas Lefèvre de Lezeau - Fabrice Micallef (Les Dossiers du GRIHL)
The third chapter of Marillac’s Life by Lefèvre de Lezeau is dedicated to the chancellor’s past as a member of the Catholic League. Justifying one’s membership to the catholic party was not easy in seventeenth-century France. This was because supporters of the League were described as violent fanatics or as hypocrites, thought to be corrupted by foreign powers such as Spain. Lezeau’s reappraisal of Marillac centres on the argument that the chancellor was the contingent of a “good League”, which was especially present in the Parisian parliament. According to Lezeau, this good parliamentary League saved the French monarchy at Marillac’s behest in 1593, by promulgating the famous “arrêt Lemaître.” This ruled out the possibility that the General Estates could give the royal crown to a foreign prince. I examined this source by asking three questions. 1) Is Lezeau’s work credible? The facts seem to be correct throughout. But the central argument concerning the crucial role of Marillac is not supported by any source other than himself. 2) What does this document tell us about Lezeau’s practices as a historian? A few clues lead us to believe that this text could have originally been written independently, and that Lezeau could have integrated it later on into his text on Marillac’s Life. 3) What is the writing strategy of the author? Lezeau tried to justify his rehabilitation of the “good League” by describing it as a mirror of the royalist party: as a royalist, a member of the “good League” is said to be temperate, courageous, loyal to the State, a “good Frenchman”, gallican, and opposed to Spanish ambitions. However, behind these consensual aspects, the author didn’t question the legitimacy of the League; he even described it as God’s primary tool for establishing peace in France. Lezeau covertly undermined the basis of bourbonian historiography. In doing this it offered devout readers the option of considering this episode of the league’s history as a spiritual and political victory rather than as a failure.